Design optimization of real estate tax and effect analysis in China - Jingjiuan Guo; Aibo Hao; Yipeng Ren (Journal of Industrial Engineering and Management (JIEM), 2014)
Purpose: The objective of this research is to reform the current real estate tax system and establish the real estate tax system suitable for China's national conditions. Design/methodology: Based on the necessity of the real estate tax reform, the paper studies the system optimization and its effects analysis of the real estate tax. At last, the paper uses the system dynamics to demonstrate the feasibility of the real estate tax from an empirical point. Findings: With the system dynamics, we can establish the causal relationship of the influence factors and forecast the impact on the future real estate prices. It can also provide some suggestions for China's real estate tax reform. Research limitations/implications: The establishment of the model might not be very mature, so we need the further study and improvement. Originality/value: This study was the first to use system dynamics to analyze the impact of real estate taxes on real estate prices, and we hope to provide some suggestions for China's real estate tax reform.
Keywords: 650; real estate tax; design optimization; effect analysis; system dynamics